INOVASI BERBASIS DIGITAL ONLINE UNTUK EFEKTIFITAS SISTEM MANAJEMEN TERINTEGRASI - Arif, Maftuhin Praharasty; djatmiko, budi (Jurnal Manajemen dan Profesional, 2024)
Stakeholders hope that their requirements and expectations will be understood and fulfilled. One of the requirements from stakeholders is related to standardization and certification of the company's products and operational processes. PLN, with its very complex business processes, is also affected by the consequences of demands for various standardizations and certifications, so efforts must be made to fulfill various permits, standardizations and certifications. In the end, managing and monitoring this matter requires large resources, not only costs but also employee time which should be allocated to more essential things in the service aspect. However, in its development, even though the stages of standardization and certification to integration have been implemented, in reality the series of management systems are still not able to eliminate the stigma of normative activities whose form is unclear, the existence and benefits of which are not well known to the staff in the unit. Therefore, the authors are trying to bring about a change in management patterns from conventional methods towards implementing online digital-based innovation in managing the integrated management system at PLN. After digital-based innovation for SMT management was implemented, it was proven to bring major and fundamental changes, including that SMT management became clear in its form and accessibility. The level of concern for collaborative development in order to fulfill requirement demands is increasing. Apart from that, the confidence of the team and management in facing audit activities shows increased readiness which is the impact of increased understanding and preparedness for well-documented evidence.